Teaching design and study of the characteristic module of maternal and infant nursing based on "high-level, innovative and challenging" (基于"两性一度"的母婴护理特色模块教学设计与研究) - HOU Xiaoni (侯小妮); LIU Hong (刘宏); XU Yang (徐杨); CHEN Yanting (陈延亭); SUN Ruiyang (孙瑞阳); MA Yuqi (马誉萁); JIN Ningning (金宁宁) (Association of Integrative Nursing, 2022)
Objective To form a maternal and infant nursing teaching plan based on" high-level, innovative and challenging" and improve overall teaching quality of obstetrics and gynecology nursing. Methods Taking the curriculum of Puerperium Management as an example, guided by the core competence of midwives and " high-level, innovative and challenging", the research group analyzed the nursing teaching documents and collected postpartum maternal-infants nursing-related literature, guidelines and evidence-based recommendations issued by authoritative organizations at home and abroad. After two rounds discussion, a teaching design was established. Results The teaching content of puerperium management is divided into 2 modules. The first teaching content is postpartum women's care, including the physical and mental changes of puerperium women and related nursing management. The length of time in teaching a theoretical class is 2 hours, and learning objectives are nursing in different periods of postpartum, the identification and assessment of abnormal problems and the multiple attributes of confinement nursing. The second teaching content is breastfeeding, including breastfeeding preparation and consultation, early promotion of breastfeeding strategies, nursing of common breastfeeding problems. The length of time in teaching a practice class is 4 hours, and learning objectives focus on breastfeeding problem assessment and resolution, non-violent communication skills and evidence-based thinking training. The learning process includes self-directed learning, case discussions, and flipped classrooms. The evaluation methods include knowledge assessment, oral presentation, breastfeeding simulation consultation and guidance, and review assignments. Conclusion Fully excavate non-high-risk maternal and infant nursing teaching advanced, high-level and challenging degree, highlight thinking and ability training, which has reference significance for obstetrics and gynecology nursing teaching. (目的 形成基于"两性一度"的母婴护理特色教学方案, 为提升妇产科护理课程整体教学质量提供基础。方法 组建课题研究小组, 以"产褥期管理"为例, 以助产士核心胜任力为指引, 以"两性一度"为指引, 在分析解读行业文件和教材内容的基础上, 收集国内外产后母婴护理相关文献, 权威机构发布的指南及循证建议, 经课题组两轮讨论, 形成教学设计方案。结果 产褥期管理教学内容分2个模块: 一为产后妇女护理, 包括产褥期妇女身心变化及产褥期妇女护理, 理论课2个学时, 学习目标突出产后不同时段护理重点、异常问题识别与评估及月子护理多重属性; 二为母乳喂养, 包括母乳喂养准备与咨询, 早期促进母乳喂养策略、常见母乳喂养问题护理, 实验课4个学时, 学习目标注重母乳喂养问题评估与解决、非暴力沟通技巧及循证思维培养。学习过程与方式包括自主学习、案例讨论、翻转课堂, 评价方式包括知识测评、口头汇报、母乳喂养模拟咨询与指导、综述作业等。结论 充分挖掘母婴护理教学的先进性、高阶性和挑战度, 突出思维和能力培养, 对妇产科护理教学有借鉴意义。)